FEATURES OF CONTROLLING ELECTROPNEUMATIC VALVES OF ACTUATOR TO CONTROL ITS CLUTCH WITH ACCELERATION VALVE - O. A. Yaryta; M. G. Mychalevych; D. N. Leontiev; V. I. Klymenko; V. A. Bogomolov; I. V. Gritsuk; Y. B. Novikova (Наука и техника)
The article deals with one of the ways to control an actuator of the automated clutch control system. The aim is to design control of the electropneumatic actuator, to control its coupling with the acceleration valve on the basis of experimental research as well as to provide rational parameters of the automated clutch control system for the robotic transmission. The feature of the system is an acceleration valve in the design of the electropneumatic actuator to control the clutch. New links demand to adjust the way to control the actuator. The connection of Pulse-Width Modulation (PWM) with single power supply pulses to control electropneumatic valves is substantiated. The quantitative characteristics of single control pulses and PWM ones are determined. The error of operation accuracy for various ways of the control of the electropneumatic actuator to control the clutch of the robotic transmission is determined. Obtained separate PWM area is designed to suppress the initial hysteresis when the rod of the clutch actuator is moved. An algorithm for the operation of a clutch control system is proposed, taking into account the use of two modes of operation of solenoid valves. A graphical interpretation of the clutch control algorithm is presented, which gives an idea of the location of the constant signal feeding zones to the solenoid valve, as well as the operation areas of the solenoid valve in PWM mode. The control algorithm of the clutch booster provides a mode of guaranteed absence of excess pressure in the pneumatic cylinder after releasing the clutch pedal, provided that two normally closed solenoid valves are used. This configuration of the electro-pneumatic clutch control system allows the use of an emergency clutch release system in case of voltage absence. The reference algorithm for filtering the array of data coming from the feedback sensor, as well as the numerical values of the delay caused by the presence of a filter, are given.